Methodology for generating chorioallantoic membrane patient-derived xenograft (CAM-PDX) models of pleural mesothelioma and performing preclinical imaging for the translation of cancer studies and drug screening. [version 2; peer review: 2 approved] - Judy M Coulson; Joseph J Sacco; Michael Shackcloth; Alexander Haragan; Doris M Rassl; Harish Poptani; Anne Herrmann; Liam Shaw; Sarah Barnett; Jan Schulze (F1000Research)
Background Pleural mesothelioma is a cancer of the lung lining associated with asbestos exposure. Platinum/pemetrexed chemotherapy has been used for many years but provides little benefit and, despite recent immunotherapy advances, prognosis remains poor underpinning the need for development of novel therapeutics or drug repurposing. Fertilized hens’ eggs provide a rapid and cost-effective alternative to murine models of pleural mesothelioma which are commonly used in preclinical studies, with chorioallantoic membrane (CAM) xenografts being a partial replacement for mouse flank xenografts. Here we describe methods to generate mesothelioma patient-derived xenografts on the CAM (CAM-PDX), and to subsequently assess these PDX nodules by preclinical imaging and histology. Methods Fragments of surplus mesothelioma tissue obtained from patient biopsies were implanted onto the CAM on embryonic day 7 (E7), fresh or following cryopreservation, with the established PDX dissected on E14 and fixed for histological/immunohistochemical analysis. The optimal freezing method was determined by comparing tissue integrity and cellular content of cryopreserved tissue fragments with paired fresh samples via histological/immunohistochemical analyses. [18F]-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) was used to assess viability of PDXs in ovo. Results Methodologies for processing, cryopreservation, re-animation, and engraftment of mesothelioma tissue fragments were established. Cryopreservation of biopsy samples and parallel processing of contiguous sections allows for assessment of mesothelioma cellularity. CAM-PDXs, generated from fresh or slow-frozen tissue, were well vascularized whilst maintaining the architecture and cellular composition of the patient tissue. Furthermore, uptake of [18F]-FDG following intravenous injection could be visualized and quantified. Conclusions The CAM is a rapid platform for engrafting patient-derived tissue, maintaining elements of the tumor microenvironment and recapitulating heterogeneity observed in mesothelioma. Combining the CAM-PDX model and FDG-PET/CT provides a quantitative in vivo platform for pre-screening of novel treatment strategies and drug combinations, with the potential for development of patient tumor avatars for predicting clinical response.